Optimasi Formula Sediaan Toner Tea Tree Oil (Melaleuca alternifolia (Maaiden & Betche) Chell) dengan Variasi Gliserin Dan Propilen Glikol Menggunakan Metode Simplex Lattice Design - Adityas, Hanung Puspita; Wulansari, Eka; Fitria, Sabila Nur (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2024)
Toner formulation is created using a combination of glycerin and propylene glycol. Glycerin can activate transglutaminase activity in the stratum corneum, increase the corneocyte maturation process and reduce scaling in xerotic skin. Propylene glycol is a penetration enhancer so it is usually used as a solvent and carrier for substances that are not soluble in water. As part of the formulation developement, the product is formulated as a toner. This research aims to determine the optimum composition of the toner formula with variation in the concentrations of glycerin and propylene glycol to achieve the optimal formula. This research uses the Simplex Lattice Design method. The evaluation tests carried out were organoleptic, specific gravity, viscosity, pH, transferred volume and hedonic tests. The organoleptic test results are white with a liquid texture and a distinctive aroma of tea tree oil. The specific gravity results meet the range between 1.01-1.1. The panelists' hedonic test results preferred the color and texture/shape of the tea tree oil toner, while the aroma preferred the comparison toner. Optimizing the optimum formula resulted in 12% glycerin and 8% propylene glycol with predicted values of pH 5.91, viscosity 3.70, and volume transferred 95.84. The optimum formula shows an average replication of 1.2 and 3 in the pH test of 5.84, viscosity of 3.76 and volume transferred 96. The results of the optimum formula and predicted values were analyzed using the One Sample T-Test, and the results showed that there were no significant differences. (p>0.05) namely pH test 0.981; viscosity 0.899; and the volume moved was 0.408. The conclusion of this research is that the tea tree oil toner preparation obtained an optimum formula with a ratio of 12% glycerin and 8% propylene glycol.